Gaming as a Medium for the Expression of Citizens' Views on Environmental Dilemmas. - Griffiths, Dai; Ower, Jude; Hollins, Paul; Garg, Anchal (UNIR, 2026)
The decline of traditional media and channels of communication has led to policymakers experiencing difficulty in understanding public sentiment. A case study was conducted to explore how games-based activities can be used to provide a link between citizens and policy makers. A system developed by PlanetPlay, and extended in the GREAT project, was used to embed a survey in the game SMITE. The intervention and survey questions were designed in collaboration with the United Nations Development Programme (UNDP) and the Hi-Rez game studio. The effectiveness of the infrastructure and the collaborative approach were demonstrated. The results revealed some significant differences in views on climate change between different age groups, genders, and education level. However, the data was heavily skewed towards males in the 18-35 age group, and to respondents in the United States, which limited the generalizability of the findings. It was concluded that in-game placement in collaboration with games studios is more effective than paid placement, and that a wider variety of games is needed to ensure that a study has an adequate range of respondent profiles. Finally, reflections are offered on the possible role of artificial intelligence in gathering such data.
Keywords: Citizen Engagement; Games; Gamification; Policymaker; Survey